Upaya Peningkatan Perilaku Hidup Sehat melalui Program Community-Led Total Sanitation kepada Masyarakat Desa Tumpang, Malang - Nurnaningsih Herya Ulfah; Suci Puspita Ratih; Mika Vernicia Humairo; Dian Puspitaningtyas Laksana; Ilham Budi Prasojo; Lintang Pakerti Esa Wahyu Aji (Warta LPM, 2024)
The practice of open defecation remains prevalent in Ledoksari Hamlet, Tumpang Village, Malang Regency. This behavior persists because open defecation has become a normalized culture or habit among the local community. Therefore, a change effort is needed through the implementation of the Community-Led Total Sanitation Approach by the Community Service Team of Universitas Negeri Malang. This program aims to educate the community about the impacts of open defecation. The method used in this program employs a triggering approach that directly involves the community, with stages including pre-triggering, triggering, and post-triggering activities. The outcomes of this initiative reveal an increase in participants knowledge regarding environmental health. Interactive discussions were also conducted by the service team to allow participants to voice their aspirations, which were then communicated to stakeholders. The service team further recommended the implementation of the "Arisan Jamban" program. This program encourages community members to organize activities that promote clean and healthy living behaviors within their environment. Aligned with the first pillar of the Community-Based Total Sanitation (STBM) initiative, which is to stop open defecation, the "Arisan Jamban" program can be utilized as a viable solution to reduce water source contamination.